Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Effects of feeding forage rape or chicory in a grass silage and concentrate-based diet as supplementary crops to replace irrigated pasture on performance, rumen metabolism and microbiome - Juan P. Keim; Natalia Quezada; Sandra Salazar; Rubén G. Pulido; Paul Maclean; David Pacheco; Nikola Palevich; Silvana Bravo; Camila Muñoz; Einar Vargas-Bello-Pérez (Animal Feed Science and Technology, 2025)

A new Neu—a syngeneic model of spontaneously metastatic HER2-positive breast cancer - Aaron G. Baugh; Edgar Gonzalez; Valerie H. Narumi; Jesse Kreger; Yingtong Liu; Christine Rafie; Sofi Castanon; Julie Jang; Luciane T. Kagohara; Dimitra P. Anastasiadou; James Leatherman; Todd Armstrong; et al. (Clinical & Experimental Metastasis, 2024)
Metastatic disease results from the dissemination of tumor cells beyond their organ of origin to grow in distant organs and is the primary cause of death in patients with advanced breast cancer. Preclinical murine models in which primary tumors spontaneously metastasize are valuable tools for studying metastatic progression and novel cancer treatment combinations. Here, we characterize a novel syngeneic murine breast tumor cell line that provides a model of spontaneously metastatic neu-expressing breast cancer with quicker onset of widespread metastases after orthotopic mammary implantation in immune-competent NeuN mice. The NT2.5-lung metastasis (-LM) cell line was derived from serial passaging of tumor cells that were macro-dissected from spontaneous lung metastases after orthotopic mammary implantation of parental NT2.5 cells. Within one week of NT2.5-LM implantation, metastases are observed in the lungs. Within four weeks, metastases are also observed in the bones, spleen, colon, and liver. We demonstrate that NT2.5-LM metastases are positive for NeuN—the murine equivalent of human epidermal growth factor 2 (HER2). We further demonstrate altered expression of markers of epithelial-to-mesenchymal transition (EMT), suggestive of their enhanced metastatic potential. Genomic analyses support these findings and reveal enrichment in EMT-regulating pathways. In addition, the metastases are rapidly growing, proliferative, and responsive to HER2-directed therapy. The new NT2.5-LM model provides certain advantages over the parental NT2/NT2.5 model, given its more rapid and spontaneous development of metastases. Besides investigating mechanisms of metastatic progression, this new model may be used for the rationalized development of novel therapeutic interventions and assessment of therapeutic responses.

Additive and non-additive genetic variance in juvenile Sitka spruce (Picea sitchensis Bong. Carr) - J.J. Ilska; D.J. Tolhurst; H. Tumas; J. P. Maclean; J. Cottrell; S.J. Lee; J. Mackay; J.A. Woolliams (Tree Genetics & Genomes, 2023)
Many quantitative genetic models assume that all genetic variation is additive because of a lack of data with sufficient structure and quality to determine the relative contribution of additive and non-additive variation. Here the fractions of additive ( f a ) and non-additive ( f d ) genetic variation were estimated in Sitka spruce for height, bud burst and pilodyn penetration depth. Approximately 1500 offspring were produced in each of three sib families and clonally replicated across three geographically diverse sites. Genotypes from 1525 offspring from all three families were obtained by RADseq, followed by imputation using 1630 loci segregating in all families and mapped using the newly developed linkage map of Sitka spruce. The analyses employed a new approach for estimating f a and f d , which combined all available genotypic and phenotypic data with spatial modelling for each trait and site. The consensus estimate for f a increased with age for height from 0.58 at 2 years to 0.75 at 11 years, with only small overlap in 95% support intervals ( I 95 ). The estimated f a for bud burst was 0.83 ( I 95 =[0.78, 0.90]) and 0.84 ( I 95 =[0.77, 0.92]) for pilodyn depth. Overall, there was no evidence of family heterogeneity for height or bud burst, or site heterogeneity for pilodyn depth, and no evidence of inbreeding depression associated with genomic homozygosity, expected if dominance variance was the major component of non-additive variance. The results offer no support for the development of sublines for crossing within the species. The models give new opportunities to assess more accurately the scale of non-additive variation.

Network Analysis Reveals Changes in Dietary Intakes and DNA Methylation in Inflammatory and Obesity-related Cancer Pathways Are Associated with Improvements in Clinical Health Indicators During Behavioral Weight Loss - E. Hill; J. Siebert; I. Konigsberg; P. Jambal; M. Stanislawski; D. Ostendorf; K. Bing; L. Wayland; J. Scorsone; D. Bessesen; P. MacLean; E. Melanson; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Monitoring heat strain: the effect of sensor type and location on single-site and mean skin temperature during work in the heat - Benjamin L. MacLean; Kendal MacLean; Ian B. Stewart; Andrew P. Hunt (International Archives of Occupational and Environmental Health, 2021)

The problem of scale in predicting biological responses to climate - Luca Bütikofer; Karen Anderson; Daniel P. Bebber; Jonathan J. Bennie; Regan I. Early; Ilya M. D. Maclean (Global Change Biology, 2020)
Many analyses of biological responses to climate rely on gridded climate data derived from weather stations, which differ from the conditions experienced by organisms in at least two respects. First, the microclimate recorded by a weather station is often quite different to that near the ground surface, where many organisms live. Second, the temporal and spatial resolutions of gridded climate datasets derived from weather stations are often too coarse to capture the conditions experienced by organisms. Temporally and spatially coarse data have clear benefits in terms of reduced model size and complexity, but here we argue that coarse‐grained data introduce errors that, in biological studies, are too often ignored. However, in contrast to common perception, these errors are not necessarily caused directly by a spatial mismatch between the size of organisms and the scale at which climate data are collected. Rather, errors and biases are primarily due to (a) systematic discrepancies between the climate used in analysis and that experienced by organisms under study; and (b) the non‐linearity of most biological responses in combination with differences in climate variance between locations and time periods for which models are fitted and those for which projections are made. We discuss when exactly problems of scale can be expected to arise and highlight the potential to circumvent these by spatially and temporally down‐scaling climate. We also suggest ways in which adjustments to deal with issues of scale could be made without the need to run high‐resolution models over wide extents.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Biochemical pathways to α-ketoglutarate, a multi-faceted metabolite - F. Legendre; A. MacLean; V. P. Appanna; V. D. Appanna (World Journal of Microbiology and Biotechnology, 2020)

Invasion by Rhododendron ponticum depletes the native seed bank with long-term impacts after its removal - Janet E. Maclean; Ruth J. Mitchell; David F. R. P. Burslem; David Genney; Jeanette Hall; Robin J. Pakeman (Biological Invasions, 2018)

Determinants of woody encroachment and cover in African savannas - Aisling P. Devine; Robbie A. McDonald; Tristan Quaife; Ilya M. D. Maclean (Oecologia, 2017)

Fine‐scale climate change: modelling spatial variation in biologically meaningful rates of warming - Ilya M. D. Maclean; Andrew J. Suggitt; Robert J. Wilson; James P. Duffy; Jonathan J. Bennie (Global Change Biology, 2017)
The existence of fine‐grain climate heterogeneity has prompted suggestions that species may be able to survive future climate change in pockets of suitable microclimate, termed ‘microrefugia’. However, evidence for microrefugia is hindered by lack of understanding of how rates of warming vary across a landscape. Here, we present a model that is applied to provide fine‐grained, multidecadal estimates of temperature change based on the underlying physical processes that influence microclimate. Weather station and remotely derived environmental data were used to construct physical variables that capture the effects of terrain, sea surface temperatures, altitude and surface albedo on local temperatures, which were then calibrated statistically to derive gridded estimates of temperature. We apply the model to the Lizard Peninsula, United Kingdom, to provide accurate (mean error = 1.21 °C; RMS error = 1.63 °C) hourly estimates of temperature at a resolution of 100 m for the period 1977–2014. We show that rates of warming vary across a landscape primarily due to long‐term trends in weather conditions. Total warming varied from 0.87 to 1.16 °C, with the slowest rates of warming evident on north‐east‐facing slopes. This variation contributed to substantial spatial heterogeneity in trends in bioclimatic variables: for example, the change in the length of the frost‐free season varied from +11 to −54 days and the increase in annual growing degree‐days from 51 to 267 °C days. Spatial variation in warming was caused primarily by a decrease in daytime cloud cover with a resulting increase in received solar radiation, and secondarily by a decrease in the strength of westerly winds, which has amplified the effects on temperature of solar radiation on west‐facing slopes. We emphasize the importance of multidecadal trends in weather conditions in determining spatial variation in rates of warming, suggesting that locations experiencing least warming may not remain consistent under future climate change.

Estimation of potential impacts of climate change on growth and yield of temperate tree species - M. Irfan Ashraf; Charles P.-A. Bourque; David A. MacLean; Thom Erdle; Fan-Rui Meng (Mitigation and Adaptation Strategies for Global Change, 2015)

Papyrus swamp drainage and the conservation status of their avifauna - Ilya M. D. Maclean; Jeremy P. Bird; Mark Hassall (Wetlands Ecology and Management, 2014)

Ova fecundity in Scottish Atlantic salmon Salmo salar : predictions, selective forces and causal mechanisms - P. J. Bacon; J. C. MacLean; I. A. Malcolm; W. S. C. Gurney (Journal of Fish Biology, 2012)
Ova fecundities of Scottish Atlantic salmon Salmo salar , predicted from log 10 regression of ova numbers and female fork length ( L F ), differed widely between upland and lowland stocks within the same river, whereas sea‐age, river and year factors had insignificant effects on fecundity once L F was accounted for. For upland fish, the relationship between log 10 L F and log 10 ova mass ( M O ) was stable between two datasets collected 40 years apart. Although upland and lowland females both produced comparable log 10 M O (log 10 L F ) −1 , lowland females partitioned this into 45% more, but smaller ova, whereas upland females produced fewer, but larger, eggs. The possible causes and implications of this are discussed for evolutionary perspectives (lifetime production), population structure (local tributary v. large catchments; environmental effects), population dynamics and stability (density‐dependent control mechanisms) and fisheries management (stock–recruitment; short and long‐term stock sustainability).

Co-regulation of nuclear genes encoding plastid ribosomal proteins by light and plastid signals during seedling development in tobacco and Arabidopsis - Daniel MacLean; Cheryl A. Jerome; Anthony P. C. Brown; John C. Gray (Plant Molecular Biology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Correlating Material Properties with Tissue Composition in Enzymatically Digested Bovine Annulus Fibrosus and Nucleus Pulposus Tissue - Delphine S. Perie; Jeff J. Maclean; Julia P. Owen; James C. Iatridis (Annals of Biomedical Engineering, 2006)

Salicylic acid mediates resistance to the vascular wilt pathogen Fusarium oxysporum in the model host Arabidopsis thaliana - C. I. Edgar; K. C. McGrath; B. Dombrecht; J. M. Manners; D. C. Maclean; P. M. Schenk; K. Kazan (Australasian Plant Pathology, 2006)

Phylogeography, genetic structure, and diversity in the dhole ( Cuon alpinus ) - A. IYENGAR; V. N. BABU; S. HEDGES; A. B. VENKATARAMAN; N. MACLEAN; P. A. MORIN (Molecular Ecology, 2005)
The Asiatic wild dog or dhole was once very widely distributed across Asia but now has a very fragmented range. In this first genetic study of this little‐known species, we obtained information on genetic diversity, phylogeography, and social structure using both mitochondrial control region sequencing and microsatellite genotyping of noninvasive faecal samples from wild populations, as well as from museum and captive samples. A pattern largely consistent with isolation by distance across the Asian mainland was observed, with no clear subspecies distinctions. However, two major phylogeographical groupings were found across the mainland, one extending from South, Central, and North India (south of the Ganges) into Myanmar, and the other extending from India north of the Ganges into northeastern India, Myanmar, Thailand and the Malaysian Peninsula. We propose a scenario involving glaciation events that could explain this pattern. The origin of the dhole populations in Sumatra and Java is enigmatic and requires further study. Very low levels of genetic diversity were observed among wild dholes from Baluran National Park in Java, Indonesia, but in contrast, high levels were observed in Mudumalai Wildlife Sanctuary in South India.

Estimation of the repeatability and reproducibility of three diagnostic tests for infectious salmon anaemia virus - P Nérette; I Dohoo; L Hammell; N Gagné; P Barbash; S MacLean; C Yason (Journal of Fish Diseases, 2005)
Reverse transcriptase polymerase chain reaction (RT‐PCR), virus isolation (VI) and indirect fluorescent antibody tests (IFAT) are three assays currently used by the salmon industry to identify fish infected with infectious salmon anaemia virus (ISAV). However, no data are available on the repeatability (within‐laboratory consistency) and reproducibility (between‐laboratory consistency) of these assays and very limited information is available on the effect of freezing samples on test results. In order to evaluate these assays, five laboratories participated in a blinded study of 400 kidney samples representing four populations of farmed Atlantic salmon with different prevalence of ISAV. Each laboratory used its own testing protocols. Repeatability and reproducibility were evaluated using kappa as the measure of agreement. The effect of freezing was evaluated using the McNemar test. Freezing did not affect VI but improved the sensitivity of RT‐PCR. The repeatability and reproducibility of VI was almost perfect. There was a substantial difference in repeatability of RT‐PCR among the three laboratories with kappa ranging from 0.5 to 0.96. The repeatability for RT‐PCR was generally low. The repeatability of IFAT was moderate when the results were analysed using 1+ and above as a positive result. The results of the study show the need to standardize the protocol and interpretation of RT‐PCR.

Effects of spaceflight on myosin heavy-chain content, fibre morphology and succinate dehydrogenase activity in rat diaphragm - Ian M. MacLean; Charles T. Putman; Gregory Hansen; Gordon J. Bell; Karen J. B. Martinuk; Thomas P. Martin (Pflügers Archiv - European Journal of Physiology, 2004)

Five new polymorphic microsatellite loci in the European hedgehog Erinaceus europaeus - M. Henderson; S. A. Becher; C. P. Doncaster; N. Maclean (Molecular Ecology, 2000)

Methylglyoxal production in bacteria: suicide or survival? - G. P. Ferguson; S. Tötemeyer; M. J. MacLean; I. R. Booth (Archives of Microbiology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Genetic structure of an aphid studied using microsatellites: cyclic parthenogenesis, differentiated lineages and host specialization - P. Sunnucks; P. J. De Barro; G. Lushai; N. MacLean; D. Hales (Molecular Ecology, 1997)
In a previous study, samples of the grain aphid Sitobion avenae (F.) were collected from wheat and adjacent cocksfoot hosts in a population thought to be primarily parthenogenetic, and DNA from individual aphids was analysed with a multilocus technique. Here we have applied single‐locus microsatellites and a mitochondrial DNA marker to a subset of the same DNA extracts, and have made several additional inferences about important genetic and population processes in S. avenae . Microsatellite analysis indicated very high levels of genic and genotypic variation. S. avenae fell into three genotypic groups inferred to be almost noninterbreeding, while analysis of linkage and Hardy‐Weinberg equilibria suggested high levels of sexual recombination within each genotypic group. Host specialization was evident: one lineage was found only on wheat, and one (bearing many alleles inferred to be introgressed from the blackberry‐grass aphid S. fragariae (Walker)) was found only on cocksfoot. The third group of interrelated genotypes was found commonly on both hosts. Although most genotypes were found only once, some were much more numerous in the sample than expected from the frequency of the alleles they contained. This, and rapid temporal changes in genotypic composition of samples, indicates strong selective differences between genotypes and lineages. In the major genotypic group, the commonest genotypes were significantly more homozygous than were rare ones: thus these data may help to explain the frequent observation of homozygous excess in aphid allozymes. The genotype group showing S. avenae ‐like as well as S. fragariae ‐like alleles also carried S. fragariae ‐like mitochondrial DNA in at least 25/31 cases, indicating gender‐asymmetrical hybridization.